Complex Convexity of Orlicz Modular Sequence Spaces. (10th November 2016) - Chen, Lili; Chen, Deyun; Jiang, Yang
Abstract : The concepts of complex extreme points, complex strongly extreme points, complex strict convexity, and complex midpoint locally uniform convexity in general modular spaces are introduced. Then we prove that, for any Orlicz modular sequence space l Φ, ρ, l Φ, ρ is complex midpoint locally uniformly convex. As a corollary, l Φ, ρ is also complex strictly convex.